Immune Checkpoint Inhibitors for Advanced Hepatocellular Carcinoma: Monotherapies and Combined Therapies - Ouyang, Tao; Kan, Xuefeng; Zheng, Chuansheng (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide, with a high mortality rate. Liver resection, transplantation, and radiofrequency ablation are considered curative therapies for early-stage HCC. Transarterial chemoembolization is the standard treatment for intermediate-stage HCC. Systemic therapy is recommended for advanced HCC. For more than a decade, sorafenib and lenvatinib were used as the first-line treatment for the advanced HCC. For the great success of immunotherapy in melanoma and lung cancer, some immune-based treatments, such as immune checkpoint inhibitors (ICIs), have been applied in the treatment of HCC. The anti-programmed cell death protein 1 (PD1) antibodies, including nivolumab and pembrolizumab, have been approved by the Food and Drug Administration for sorafenib-pretreated patients. Moreover, due to the results of durable antitumor responses attained from the phase 3 trials, the combination of atezolizumab with bevacizumab is now the standard therapy for advanced HCC. Recently, there is a lot of clinical trials evolving the ICIs, as monotherapy or in combination with tyrosine kinase inhibitors, anti-angiogenic drugs, chemotherapeutic agents, and locoregional therapies, providing a promising outcome for advanced HCC. Thus, this review summarized the role of ICIs for HCC patients with monotherapy or combination therapy.